Investing in sustainable wildlife ranching - biosecurity threats and opportunities - Preston, Guy, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Invasive alien species are probably the single greatest threat to the sustainability of wildlife ranching in southern Africa. This talk will illustrate the exponential growth of invasives; their impacts (grazing/browsing; water security; wild fires; erosion; disease, and more), and options for their control. It will also talk to the compounding impacts of climate change, and associated bush encroachment. The opportunities to link these to other measures of sustainability (e.g. wild-fire management), and the creation of jobs (including the utilization of the biomass), will be highlighted.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.